The effects of perceived organizational support, perceived supervisor support and perceived co-worker support on safety and health compliance. Issue 3 (2nd July 2016) - Puah, Lee Na; Ong, Lin Dar; Chong, Wei Ying
Abstract : Although knowledge is cumulating, very little is known about the effects of various sources of support on safety and health compliance. This study goes beyond previous research by investigating the relationships among perceived support from organizations, supervisors and co-workers, and employees' safety and health compliance behaviour at chemical and petroleum process plants. The results of this study show that the support from organizations, supervisors and co-workers was significantly related to employees' safety and health compliance. Also, the findings reveal that perceived supervisor support has the strongest influence in ensuring employees' safety and health compliance behaviour.